The Soviet and Russian navies: From the Cold War to the Cold War 2.0, 1945-2024 - Muraviev, Alexey (2025)
This chapter examines the rise of the Soviet navy to a truly 'ocean-going' force during the Cold War, its subsequent post-Soviet fall as a Russian force and the more recent rekindling of Russian naval power under Vladimir Putin. At the end of the Great Patriotic War, the Soviet Union was not a major naval power, possessing a navy focussed on coastal defence and support of troops on land. Ambitions for a truly 'ocean-going' fleet would not be realised until the 1970s following a period of dramatic growth in Soviet naval power from the mid-1960s onwards. Drivers for this force included the need to combat US nuclear weapons at a distance from the Soviet coastline and the need to deploy and protect the naval leg of the Soviet Union's own strategic nuclear forces. The collapse of the Soviet Union meant a steep decline in post-Soviet Russian naval power, although there has been some attempt to resurrect Russian naval capabilities and reach under the government of Vladimir Putin.